Amplitude analysis of the Λ0b → pK−γ decay - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; De Cian, Michel; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Herrero Gascón, Paula; Langenbruch, Christoph; Leverington, Blake; et al. (Journal of high energy physics, 2024)
The resonant structure of the radiative decay Λ0b → pK−γ decay in the region of proton-kaon invariant-mass up to 2.5 GeV/c2 is studied using proton-proton collision data recorded at centre-of-mass energies of 7, 8, and 13 TeV collected with the LHCb detector, corresponding to a total integrated luminosity of 9 fb−1. Results are given in terms of fit and interference fractions between the different components contributing to this final state. Only Λ resonances decaying to pK− are found to be relevant, where the largest contributions stem from the Λ(1520), Λ(1600), Λ(1800), and Λ(1890) states.